2022
DOI: 10.1097/corr.0000000000002434
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Abounds in Minimum Clinically Important Differences in THA: A Systematic Review

Abstract: BackgroundThe minimum clinically important difference (MCID) is intended to detect a change in a patient-reported outcome measure (PROM) large enough for a patient to appreciate. Their growing use in orthopaedic research stems from the necessity to identify a metric, other than the p value, to better assess the effect size of an outcome. Yet, given that MCIDs are population-specific and that there are multiple calculation methods, there is concern about inconsistencies. Given the increasing use of MCIDs in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The investigators summarized evidence reporting minimum clinically important difference (MCID) estimates for knee and hip arthroplasty patient-reported outcome measures (PROMs). The titles of these papers emphasized that "discordance abounds" [2] and that there were "considerable inconsistencies" [3] in MCID estimates. We agree with this message of substantial MCID variability, a finding reported by others [8,10].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators summarized evidence reporting minimum clinically important difference (MCID) estimates for knee and hip arthroplasty patient-reported outcome measures (PROMs). The titles of these papers emphasized that "discordance abounds" [2] and that there were "considerable inconsistencies" [3] in MCID estimates. We agree with this message of substantial MCID variability, a finding reported by others [8,10].…”
Section: To the Editormentioning
confidence: 99%
“…We were struck by the conflicting messages of two recently published systematic reviews by Deckey and colleagues [2,3]. The investigators summarized evidence reporting minimum clinically important difference (MCID) estimates for knee and hip arthroplasty patient-reported outcome measures (PROMs).…”
Section: To the Editormentioning
confidence: 99%
“…We thank Dr. Riddle and Dr. Dumenci for their insightful response [7] to our systematic reviews about the use of minimum clinically important differences (MCID) for patient-reported outcome measures (PROMs) after hip and knee arthroplasty [3,4]. Much of their response focuses on inherent problems with the PROMS that have been commonly used in orthopaedic surgery, the limitations of MCIDs, as well as potential alternatives for determining meaningful changes.…”
Section: To the Editormentioning
confidence: 99%
“…The authors of this study in Clinical Orthopaedics and Related Research ® [2] conducted a systematic review of MCIDs reported in THA studies. This well-conducted methodologic review identified 242 eligible THA studies that calculated an MCID for any patient-reported outcome measure (PROM).…”
Section: Where Are We Now?mentioning
confidence: 99%
“…The authors noted that anchor-based MCIDs were larger than distribution-based MCIDs in all PROMs for which there was a direct comparison between the two approaches, indicating that the distribution-based method may underestimate the MCID. I suggest that readers of clinical research "bookmark" this CORR study [2] and keep it handy.…”
mentioning
confidence: 99%